"Bend it like beckham'" - ball rotation in the curved football kick - Whiteside, D.; Alderson, J.; Elliott, B. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
The objectives of this study were to quantify the 3D angular velocity and spin axes of a curved versus straight kick for goal in football. A 12 camera 250 Hz 3D Vicon motion analysis system recorded 4 semi-professional soccer players, as they performed 5 straight (S) and 10 curved (C) kicks. While the velocity of the ball was similar for both kicks (~20 m.s-1), spin rate was significantly different (S=22.6 rad.s-1; C=36.4 rad.s-1). While the level of spin for the straight kick was surprising, the elevation angle of its spin axis was significantly lower in the straight compared with curved kicks (S=30.4°; C=62.6°)